COVID-19: Context, Impact, Lessons Learned, Tourism Trends and Policy for Tourism-industry Recovery - Hong Long, Pham; Viet Anh, Ngo (VNU Journal of Science: Policy and Management Studies, 2022)
COVID-19 is an infectious pandemic with far-reaching global consequences, affecting nearly every economic, cultural, social, and environmental area. The COVID-19 epidemic has wreaked havoc on the tourism sector, causing millions of people to lose their jobs and income all around the world. In order to assist the tourism industry to recover from the COVID-19 epidemic, Vietnam's tourism industry must acknowledge and re-evaluate tourism management and development. This research evaluated the economic, social, and environmental implications on the tourism industry worldwide and in Vietnam, as well as the Government of Vietnam's plans, policies, and strategies for safe adaptation and flexibility in reviving Vietnam's tourism business in the current circumstances. In addition, the report offers suggestions for reviving tourism.